Effects of Climate Change on Agriculture in Pakistan: A Social Media Analysis - Muhammad Rashid Khan (Journal of Peace, Development and Communication, 2023)
Social Media has become an important element of our life as we depend on it for getting information about every aspect of life. Given study was aimed to find association between social media reporting of climate change and pattern of attitudes by the farmer in the Punjab province of Pakistan. Correlation-experimental research design was used to found the relations and effects of climate change on agriculture. Purposive sampling technique was used to collect sample of 120 male farmers from all cities of Punjab with age ranging (30-80) years. Online survey questionnaires in form of Google doc was used to collect participants’ response of what type of behaviour they used to adopt when got information of climate change through social media. Two Self-constructed questionnaires (i) Measuring of Farmer’s Behaviour Influenced by Social Media Reporting of Climate and (ii) Effects of Social Media Reporting of Climate Chang on Agriculture were used after finding its reliability and validity through piloting. Data was analyzed by using SPSS-21. Correlation Analysis was done to find out the relationship between social media reporting and Farmers’ behaviour, Linear Regression was used to find predicting social media reporting of climate change farmer’s attitude to adopt precautions to increase annual yield and agricultural production in Punjab. Discussion and conclusions was made on results obtained. Results of the study would be applied to increase agricultural and rate of annual yield through productive adaptations of behaviour of farmers.